The Economic Crisis in the Russian Mass Media: Constructing and Deconstructing Problems - Bogomazova Liudmila (Journal of Economic Sociology, 2019)
This article discusses the process of constructing the image of the economic crisis in Russian online newspapers. The relevance of such analysis is due to the increasing audience attention toward economic discussions in the media during the period of economic instability and, accordingly, the increasing influence of the media on the perception of the situation in the country. This paper is based on a constructionist perspective for understanding the nature of social problems. Counter-rhetorical strategies, suggested by Ibarra and Kitsuse, are adopted to analyze the deproblematization of the economic crisis in the Russian mass media. The goal of the study was achieved by conducting a content analysis, which included the count of mentioned key words and a thematic analysis. Moreover, in order to solve one of the tasks, network analysis was used. The study demonstrates that online newspapers pay the most attention to the coverage of anti-Russian sanctions, inflation, and the ruble rate. Meanwhile, social consequences of the crisis, such as poverty and unemployment, are represented in the Russian media to a much lesser extent. The network analysis also shows that online newspapers are focused on the ruble and dollar rates, sanctions, and loans. According to the network agenda-setting theory, these «links» of economic events in publications can form certain associations among the audience regarding the causes, perpetrators, and consequences of the crisis. Thus, inflation could be caused by the weakening of ruble rate, and sanctions could be one of the causes of the crisis. Strategies of economic crisis de-problematization or counter-rhetorical strategies were found only in mass online newspapers. There were both sympathetic (e.g., declaring impotence, perspectivizing) and unsympathetic (e.g., counter-rhetoric of telling the anecdote, counter-rhetoric of insincerity) strategies.